Wprowadzanie pokarmów uzupełniających a ryzyko rozwoju alergii - Krogulska, Aneta; Lemańczyk, Dominika; Kuśmierek, Magdalena; Brazowski, Jerzy (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Understanding the relationship between the time of the specific foods introduction and the development of allergy could improve early prevention of atopic diseases in children. Results of studies concerning these issues are contradictory. Early introduction of foods with a high allergenic potential may decrease the risk of developing food allergy and have a role in tolerance induction. Previous approach emphasized the elimination of allergenic products whereas the current approach balances exposure and elimination or even emphasizes exposition. Mechanisms of tolerance development are not well known. It appears that the key role in tolerance development is the time and regularity of foods introduction.